2022
DOI: 10.3389/fpsyt.2022.801231
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Professional Help-Seeking Intention Toward Depression Among Community-Dwelling Populations: A Structural Equation Modeling Analysis

Abstract: BackgroundA low intention of professional help seeking hinders the effective treatment of depression. The factors are from the perspectives of the social, family, and individual; however, an understanding of how they interact to predict professional help-seeking intention (PHSI) is not clear.ObjectivesThe objectives of the study was to investigate PHSI toward depression in a Chinese community-dwelling population and construct a predictive model of the PHSI to explore the various factors involved.MethodsStratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 99 publications
1
10
0
1
Order By: Relevance
“…Furthermore, those who had a history of positive help-seeking behavior with respect to modern therapy for their condition were more likely to have sought care from a modern health institution for a later episode. This finding was in agreement with previous research conducted in China, Western Australia, and Switzerland ( 65 67 ). One explanation for this could be that individuals with mental illnesses who have a history of a positive pattern of help-seeking behavior with respect to current treatments are more likely to improve and may also be satisfied with their prior interactions.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, those who had a history of positive help-seeking behavior with respect to modern therapy for their condition were more likely to have sought care from a modern health institution for a later episode. This finding was in agreement with previous research conducted in China, Western Australia, and Switzerland ( 65 67 ). One explanation for this could be that individuals with mental illnesses who have a history of a positive pattern of help-seeking behavior with respect to current treatments are more likely to improve and may also be satisfied with their prior interactions.…”
Section: Discussionsupporting
confidence: 94%
“… 43 Professional help is known to be effective for preventing and managing mental health issues, improving understanding, coping skills, and interpersonal support, and thereby reducing suicidal thoughts. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that people’s attitudes about seeking help, as well as preferences and beliefs about treatment, have a strong influence on their help-seeking behaviors ( 34 , 35 ). In this study, among those who had not sought help, the majority did not think the help-seeking sources as useful in managing mental problems.…”
Section: Discussionmentioning
confidence: 99%